1970
DOI: 10.1128/am.19.1.14-26.1970
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic Coumermycins: Structure-Activity Relationships

Abstract: The relative antimicrobial activity of a large series of semisynthetic coumermycins has been determined. Most of the derivatives, which were 3-substituted-4-hydroxy-8-methyl-7-[3-O-(5-methyl-2-pyrrolylcarbonyl) noviosyloxy] coumarins, had an in vitro antibacterial spectrum similar to that of the parent compound, coumermycin A 1 , but were generally less potent in minimal inhibitory concentration (MIC) tests. Derivatives with an alkylcarboxamido, arylcarboxamido, or arylsulfonamido group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…185,186 However, the strong serum binding of this large molecule has been advanced as the cause of its lack of effect in vivo. 187 Extensive studies of the antibacterial mechanism of action of novobiocin (1) and coumermycin A1 (9) demonstrated that they inhibit DNA gyrase and topoisomerase IV by binding to the ATPase domain of GyrB and ParE subunits, respectively. 7,8,70,181,188−190 A third naturally occurring coumarin, clorobiocin (10), features a structure closely related to novobiocin (1) but for a pyrrole moiety replacing the carbamate group and a chlorine atom instead of a methyl.…”
Section: Assays For Bacterial Type Iia Topoisomerase Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…185,186 However, the strong serum binding of this large molecule has been advanced as the cause of its lack of effect in vivo. 187 Extensive studies of the antibacterial mechanism of action of novobiocin (1) and coumermycin A1 (9) demonstrated that they inhibit DNA gyrase and topoisomerase IV by binding to the ATPase domain of GyrB and ParE subunits, respectively. 7,8,70,181,188−190 A third naturally occurring coumarin, clorobiocin (10), features a structure closely related to novobiocin (1) but for a pyrrole moiety replacing the carbamate group and a chlorine atom instead of a methyl.…”
Section: Assays For Bacterial Type Iia Topoisomerase Inhibitionmentioning
confidence: 99%
“…Moreover, the many effects of novobiocin ( 1 ) in models of biochemical processes, such as histone precipitation, inhibition of yeast glycyl- and leucyl-tRNA synthetases, eukaryotic topoisomerases, or HSP90, probably explain the eukaryotic toxicity of such compounds . Coumermycin ( 9 ) was also the subject of studies across the years as it demonstrated potentially useful activity in vitro. , However, the strong serum binding of this large molecule has been advanced as the cause of its lack of effect in vivo . Extensive studies of the antibacterial mechanism of action of novobiocin ( 1 ) and coumermycin A1 ( 9 ) demonstrated that they inhibit DNA gyrase and topoisomerase IV by binding to the ATPase domain of GyrB and ParE subunits, respectively. ,,,, A third naturally occurring coumarin, clorobiocin ( 10 ), features a structure closely related to novobiocin ( 1 ) but for a pyrrole moiety replacing the carbamate group and a chlorine atom instead of a methyl.…”
Section: Non-quinolone Inhibitors Of Type Iia Topoisomerasesmentioning
confidence: 99%
“…Although some ATP systems using temperature-sensitive surfactant or polymer were reported to solve this problem, 12.20 it is primarily suitable for nonpolar solute. When high efficiency is desired for polar solutes, a certain amount of ionic surfactant has to be added, , which unfavorably increases the cloud-point temperature and leads to low stability of penicillin at this temperature …”
Section: Introductionmentioning
confidence: 99%